EMPIRICAL MODELS’ APPLICABILITY FOR CALCULATING THE CENTRIFUGAL PUMP'S IMPELLERS GEOMETRIC PARAMETERS - BOSTAN, Viorel; PETCO, Andrei; ȘARAGOV, Ion (Journal of Engineering Science (Chişinău), 2023)
This paper deals with the comparison of empirical computational models used to achieve the geometrical parameters of pumps impellers with models based on Computational Fluid Dynamics (CFD) simulations and optimization algorithms. Also, the actuality of the empirical models application in modern pump manufacturing industry is analyzed. Further, an empirical model for calculating the pump impeller geometrical parameters was presented. Applying this model, the calculation of the centrifugal pump impeller parameters for CH 6,3/20 1,1-2 canned motor pump was performed. The procedure for parameterization and generation of the geometric model based on parameters obtained from this model through ANSYS DesignModeler was also presented. CFD simulation based on ANSYS CFX was used to obtain the operating characteristic of the obtained centrifugal pump impeller. The authors carried out the comparison of the results of the designed model with the original one and with the optimized impeller obtained using optimization algorithms and CFD calculations.